Consultative Policy Workshop on the Implementation of Climate-Smart Agriculture in the Potato Value Chain in Tanzania: Challenges, Barriers, and Opportunities - Osumba, Joab J.L.; Recha, John W.M.; Demissie, Teferi Dejene (Accelerating Impacts of CGIAR Climate Research for Africa, 2022)
Climate-smart interventions in agriculture, or climate-resilient agriculture, is increasingly becoming a global climate policy priority. Agriculture is increasingly gaining recognition from climate policy actors for its exposure to climate change impacts and its contribution to climate change. Investment into climate-smart agriculture (CSA) innovations are also receiving increasing attention from investors. The official climate change policy position for all countries of East Africa is to prioritize adaptation, with mitigation expected to be a co-benefit if, when and where possible.